Noninvasive vagus nerve stimulation for migraine: a systematic review and meta-analysis of randomized controlled trials - Song, Dong; Li, Piaoyi; Wang, Yonggang; Cao, Jin (Frontiers in Neurology, 2023)
Background Medication is commonly used to treat migraine. However, patients may experience adverse events or fail to respond to medication. In recent years, neuromodulation techniques have emerged as potential non-pharmacological therapy for migraine. This article focuses on a systematic review and meta-analysis of randomized controlled trials of non-invasive vagus nerve stimulation (n-VNS) for migraine to determine the efficacy, safety and tolerability of n-VNS. Methods We searched PUBMED, EMBASE, and Cochrane Center Register of Controlled Trials databases up to July 15, 2022. Primary outcomes were monthly reduced migraine/headache days, and pain-free rates within 2 h. Secondary outcomes were ≥ 50% responder rate, headache intensity, monthly acute medication reduction days, and adverse events. Results Meta-analysis shows that non-invasive cervical vagus nerve stimulation (n-cVNS) significantly impacted ≥50% responder rate (OR, 1.64; 95% CI, 1.1 to 2.47; p = 0.02), but had no significant effect on reducing migraine days (MD, −0.46; 95% CI, −1.21 to 0.29; p = 0.23) and headache days (MD, −0.68; 95% CI, −1.52 to 0.16; p = 0.11). In contrast, low-frequency non-invasive auricular vagus nerve stimulation (n-aVNS) was found to significantly reduce the number of migraine days (MD, −1.8; 95% CI, −3.34 to −0.26; p = 0.02) and headache intensity (SMD, −0.7; 95% CI, −1.23 to −0.17; p = 0.009), but not the number of acute medication days per month (MD, −1.1; 95% CI, −3.84 to 1.64; p = 0.43). In addition, n-cVNS was found safe and well-tolerated in most patients. Conclusion These findings show that n-VNS is a promising method for migraine management.